Macroeconomic convergence within SADC : implications for the formation of a regional monetary union - Johns, Michael Ryan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
Given the growing effect that globalisation and integration has had upon economies and regions, the process of monetary union has become an increasingly topical issue in economic policy debates. This has been driven in part by the experience and successes of the European Monetary Union (EMU), which is widely perceived as beneficial to member countries. The Southern African Development Community (SADC) is an example of a group of countries that has realised that there are benefits that may arise from economic integration. This paper makes use of an interest-rate pass through model to investigate whether the pass-through of monetary policy transmission in ten SADC countries has become more similar between January 1990 and December 2007 using monthly interest rate data. This is done to determine the extent of macroeconomic convergence that prevails within SADC, and consequently establish whether the formation of a regional monetary union is feasible. The results of the empirical pass-through model were robust and show that there are certain countries that have a more efficient and similar monetary transmission process than others. In particular, the countries that form the Common Monetary Area (CMA) and the Southern African Customs Union (SACU) tend to show evidence of convergence in monetary policy transmission, especially since 2000. In addition, from analysis of the long-run pass-through, the results reveal that there is evidence that Malawi and Zambia have shown signs of convergence toward the countries that form the CMA and SACU, in terms of monetary policy transmission. The study concludes that a SADC wide monetary union is currently not feasible based on the evidence provided from the results of the pass-through analysis. Despite this, it can be tentatively suggested that the CMA may be expanded to include Botswana, Malawi and Zambia.
Keywords: Southern African Development Community; Economic and Monetary Union; Common Monetary Area (Organization); Economic policy -- Africa, Southern; Monetary policy -- Africa, Southern; Monetary unions; Macroeconomics